2006
DOI: 10.1364/ol.31.003119
|View full text |Cite
|
Sign up to set email alerts
|

Assessing epithelial cell nuclear morphology by using azimuthal light scattering spectroscopy

Abstract: We describe azimuthal light scattering spectroscopy (phi/LSS), a novel technique for assessing epithelial-cell nuclear morphology. The difference between the spectra measured at azimuthal angles phi = 0 degrees and phi = 90 degrees preferentially isolates the single backscattering contribution due to large (approximately 10 microm) structures such as epithelial cell nuclei by discriminating against scattering from smaller organelles and diffusive background. We demonstrate the feasibility of using phi/LSS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Most importantly, it is obvious that azimuthally asymmetric backscattering is indicative of dysplastic progression; increased asymmetry for severely dysplastic or CIS nuclei is manifested in significantly lower correlation values and can be traced back to a more heterogeneous nuclear texture depicted in Table 2. This finding agrees well with prior observations on azimuth-resolved backscattering measurements [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most importantly, it is obvious that azimuthally asymmetric backscattering is indicative of dysplastic progression; increased asymmetry for severely dysplastic or CIS nuclei is manifested in significantly lower correlation values and can be traced back to a more heterogeneous nuclear texture depicted in Table 2. This finding agrees well with prior observations on azimuth-resolved backscattering measurements [13].…”
Section: Discussionsupporting
confidence: 93%
“…If the entire range of polar angles is considered and the integrand is properly normalized, the computed metric gives the scattering cross section that characterizes the overall scattering strength of the nuclei. As these intricate structures are not perfectly spherical and contain refractive index heterogeneities at different length scales, however, their scattering response will exhibit complex azimuthal asymmetry [12][13][14][15][16]. It may thus prove worthwhile to carry out a comprehensive two-dimensional investigation that will enable a comparative assessment of azimuthal dependence in nuclear scattering profiles.…”
Section: Introductionmentioning
confidence: 99%
“…An improved method for detecting the light scattered from the nucleus has been reported recently and will be further explored in the future. 43 Nevertheless, sensitivity of light scattering to the longitudinal and not to the cross-sectional nuclear diameter was also reported in another light scattering study that investigated nuclear morphology of T84 epithelial cells with Fourier domain low coherence interferometry. 44 Interestingly, we find through LSS and confocal microscopy that the longitudinal diameter of HPVimmortalized cells is significantly smaller than that of normal keratinocytes.…”
Section: Discussionmentioning
confidence: 79%
“…Georgakoudi et al 55 found a sensitivity of 100% and specificity of 91% for HGD versus LGD+ BE using this technique. A significant advance in LSS was reported recently by Yu et al at MIT,60 in which the backscatter spectra were measured at the tissue surface for both large and small values of the azimuthal angle between the incident light polarization and the scattering plane. This further isolated the contribution of nuclear scattering from that of other smaller organelles in the epithelial cells, as demonstrated by in vivo measurements in the colon in a small number of patients.…”
Section: Point Spectroscopiesmentioning
confidence: 97%